Magazine writing - Benson, Chris 1953-; Whitaker, Charles F. (Routledge/Taylor & Francis Group, 2014)
"What does it take to launch a career writing for magazines? In this comprehensive, up-to-date introduction to magazine writing, students will learn everything from the initial story pitch all the way through to the final production, taking with them the essential tools and skills they will need for today's rapidly changing media landscape. Written by a team of experienced writers and editors, Magazine Writing teaches the time-tested rules for good writing alongside the modern tools for digital storytelling. From service pieces to profiles, entertainment stories and travel articles, it provides expert guidance on topics such as: developing saleable ideas; appealing to specific segments of the market; navigating a successful pitch; writing and editing content for a variety of areas, including service, profiles, entertainment, travel, human interest and enterprise. Chock full of examples of published works, conversations with successful magazine contributors and bloggers, and interviews with working editors, Magazine Writing gives students all the practical and necessary insights they need to jumpstart a successful magazine writing career"--Provided by publisher.